2015
DOI: 10.1128/aem.03358-14
|View full text |Cite
|
Sign up to set email alerts
|

Syntrophic Growth of Desulfovibrio alaskensis Requires Genes for H 2 and Formate Metabolism as Well as Those for Flagellum and Biofilm Formation

Abstract: In anaerobic environments, mutually beneficial metabolic interactions between microorganisms (syntrophy) are essential for oxidation of organic matter to carbon dioxide and methane. Syntrophic interactions typically involve a microorganism degrading an organic compound to primary fermentation by-products and sources of electrons (i.e., formate, hydrogen, or nanowires) and a partner producing methane or respiring the electrons via alternative electron accepting processes. Using a transposon gene mutant library … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 46 publications
0
39
0
Order By: Relevance
“…However, these findings are not in line with the findings indicating a motile lifestyle, as it is known that the formation of mats or biofilms eventually results in motility loss (Alexandre, ). Flagella play important roles in the maintenance of the close physical contact between the syntrophic partners (McInerney et al ., ; Krumholz et al ., ), but this does not explain the high transcription rates of chemotaxis‐associated genes. However, the metatranscriptome‐based profile comprises the whole Fusobacteria bin ‐ represented population in situ .…”
Section: Resultsmentioning
confidence: 94%
“…However, these findings are not in line with the findings indicating a motile lifestyle, as it is known that the formation of mats or biofilms eventually results in motility loss (Alexandre, ). Flagella play important roles in the maintenance of the close physical contact between the syntrophic partners (McInerney et al ., ; Krumholz et al ., ), but this does not explain the high transcription rates of chemotaxis‐associated genes. However, the metatranscriptome‐based profile comprises the whole Fusobacteria bin ‐ represented population in situ .…”
Section: Resultsmentioning
confidence: 94%
“…Single-cell analysis of the expression of six target genes in a syntrophic co-culture composed of D. vulgaris and M. barkeri revealed only slight variations between mono-and co-cultures except for the Desulfovibrio DVU0148-DVU0150 genomic region that could be involved in syntrophic metabolism (Qi, Pei, Chen, & Zhang, 2014;Walker, He, et al, 2009). A recent study with D. alaskensis G20 indicated that H 2 and formate metabolism, motility by flagella, outer membrane components, as well as the capacity to form biofilms are required for syntrophic growth with butyrate-oxidizing Syntrophomonas wolfei (Krumholz et al, 2015).…”
Section: Desulfovibriomentioning
confidence: 98%
“…Desulfovibrio spp. are also well known to form stable syntrophic associations with other sulfate reducers and/or fermenters (Wallrabenstein et al, 1994;Krumholz et al, 2015). Therefore, at least some of the responding Desulfovibrio OTUs could also be involved in H 2 or formate scavenging.…”
Section: Sulfate-reducing Deltaproteobacteria Responded Strongest To mentioning
confidence: 99%